NEW TECHNOLOGIES ADOPTION: A DIGITAL TV STUDY - Piloto, Ronaldo Alípio da Costa; Ribas, José Roberto; Trinta, José Luiz; Altaf, Joyce Gonçalves; Troccoli, Irene Raguenet (Brazilian Journal of Operations & Production Management, 2015)
This paper reports on the role of socio-demographic and psychographic basis - the later achieved through the Value and Life Styles-2, or VALS-2 – as predictor of the consumers’ intention to migrate from the conventional analogical to digital TV broadcast. By means of validation, the sample was split in two groups, one used to estimate the logistic regression coefficients and the other used to confirm the model results and specification. It was observed that, among the alternatives of specification, the psychographic variable VALS-2 First Level and the demographic variables Age and Household Income provided a significant contribution on the discrimination of two segments – early adopters and non-adopters. The research concluded on the importance of using both demographic and psychographic segmentation basis in an integrated manner in order to research the attributes of consumers who declare their positive of migrating to innovating goods.